?THE UPTAKE AND Loss OF ABSORBED DISSOLVED COPPER BY CMRlAS ANGllLLAlUS FINGERLINGS - Oronsaye, J A 0; Obano, E E (Biological Sciences - PJSIR, 2000)
The uptake and loss of dissolved copper In media by the African: mud fish Clarias angullaris was studied! in water of 25mg 1-1hardness expressed as CaC03 of pH 6.8 at 27±2°C in a stanc test system. Th.euptake experiments involved exposure offish to 05, 0.75 and E_0mg Cu+z 1-1test so[utrom;; from whiclr the Irsn. absorbed! and!retained (l<}9'1'2, f 3 oro mg and L4036 mg Cut' g.-'wet fish wt, respectively, after 11 days, In the lass experiments, the fish were exposed: to 05, 0.75 and tomg Cu+l [-lfor 7 days and the surviving fisn were aITawecHo recover ill copper-free-water fOil over 20 days. Approximately 50"/••ofthe absorbed copperwas shed from all fish within 2 days ..Aftelr20 days the fish IreId!01. Il019, 0_1296and ~UOWmg Cu+I g-I wet wt from previous exposures to 05. 0i.75 and E..Omg Cu+2't-L respectivefy;